The effectiveness of management ability on firm value and tax avoidance - Maryam Seifzadeh (Journal of Risk and Financial Management, 2022)
The current study investigates the relationship between tax avoidance, management ability, and firm value. Three hypotheses are proposed to meet the paper's objective. For conducting such a practical study based on a post-event descriptive correlational approach, data are gathered from the website of the Tehran Stock Exchange during 2014-2020. A total of 183 companies were selected through the systematic elimination method and analyzed using the R statistical software. The results indicated a negative relationship between managerial ability and tax avoidance. Moreover, we find a significant negative relationship between tax avoidance and firm value. Finally, the findings argue that in companies with high-ability managers, the intensity of the negative relationship between tax avoidance and firm value is mitigated.
Keywords: 650; tax avoidance; managerial ability; firm value